Trends, development and history of children's themes, from the perspective of Sheikh Marfi Nodei - Abdullazadeh, Asst.Prof.Dr.Fouad; Mehraban, Arsh; Rahimi, Ruqia (Sulaimani Journal for Humanities)
In history, childhood is a group of times and stages that, from a historical perspective, as stages in a child's life in various societies, bring the concept of the child as a theme. In these stages, society's attitudes towards children, their role and position in the family and society, education, child-related activities and activities are interpreted; These centuries include the Middle Ages, the Renaissance and the nineteenth century, each of which carried its own characteristics and brought its own role and influence in the world of children. In this regard, Kurdish society has had its own position and role and people like Sheikh Marfi Node, feeling that children have their own position and personality and the importance of education and their desire and understanding to reach the peak Child-themed in Kurdish children's texts and writings. This article attempts to interpret the trend, development and history of child-themed Kurdish written texts with emphasis on the book of Ahmadi Sheikh Marfi Nodi and to give a scientific interpretation of the causes and consequences of this historical trend and uprising. The results of this article show that Sheikh Marfi Node, as one of the first figures in the history of Kurdish literature, has been able to become a reason for paying attention to children and the formation of a child-themed movement among Kurds.
Keywords: Ahmadi; Sheikh Marfi Node; Children; Kurdish Written Literature